DESPINNING OF THE EARTH ROTATION IN THE GEOLOGICAL PAST AND GEOMAGNETIC PALEOINTENSITIES - Denis C.; Schreider A.A.; Varga P.; Závoti J. (My University, 2002)
Length of day (l.o.d.) values deduced from fossils and tidal deposits suggest that the despinning rate was, on the average, about 5 times smaller during the Proterozoic than during the Phanerozoic and, moreover, that between 250 and 100 million years ago, there was a slight non-linear variation super-imposed on the overall linear trend of the Earth's rotation rate. To explain these observational facts, it has recently been argued that formation of the inner structure of the Earth (mass redistribution within the mantle and/or core formation) had not been fully completed before the Proterozoic, and that the decrease of the inertia moment associated with the evolving terrestrial interior compensated to some extent the rotational effects of tidal friction. There is an another plausible explanation to account for the difference of despinning rates during the Proterozoic and Phanerozoic, namely: the distribution of the continents had been significantly different during these epochs and the world ocean had been much shallower in the Proterozoic than in the Phanerozoic. We used published data for the Phanerozoic, Proterozoic and Archean in order to check whether there had been significant long-term changes of geomagnetic intensity. Our results are based on robust statistical analysis; they indicate that during a time interval coinciding roughly with the Mesozoic, the geomagnetic dipole moment underwent a minimum in a quite similar way as the l.o.d. data. For the Proterozoic (2500–570 million years ago) and the late Archean (3000–2500 million years ago), it is very difficult to draw a conclusion concerning the variation in time of the intensity of the geomagnetic field: the data set we used is incomplete and the statistical scatter is larger than the derived mean value. Nevertheless, we tentatively conclude that the values of the average geomagnetic moment were approximately the same in the Phanerozoic and in the Proterozoic+late Archean, and that there is no significant long-term change in the geomagnetic intensity detectable before the Phanerozoic.